Refleksi Nilai Huyula di balik Praktik Akuntansi oleh Pengusaha Depot Air Minum - Thalib, Mohamad Anwar; Kumadji , Dimas; Edis , Edis; Saikim, Fitri S. (Goodwood Akuntansi dan Auditing Reviu, 2023)
Purpose: This research aims to photograph the accounting implemented by Drinking Water Depot entrepreneurs, which requires local wisdom values Methodology/approach: this research uses a spiritual (Islamic) paradigm. Islamic ethnomethodology is the approach. The type of method used is qualitative. There are two types of data collection in the form of: structured interviews and passive participant observation. The informants were selected using a purposive sampling technique. Results/findings: The study shows two accounting practices by Drinking Water Depot entrepreneurs, namely capital accounting practices. The capital used by Drinking Water Depot entrepreneurs comes from bank loans, leasing, and personal money. Furthermore, accounting practice takes the form of a simple recording method; Drinking Water Depot entrepreneurs carry out simple records on paper, and other informants only record accounting related to business development capital in memory. This accounting practice lives with local cultural values in the form of huyula (help). This value is reflected in establishing a Drinking Water depot business, which is not limited to obtaining material benefits but also aims to help residents obtain clean water closer to where they live. Limitations: the limitations of this research lie in the informants; this study has not provided information from drinking water depot users/customers Contribution: the contribution of this research is to present the concept of accounting practices by Drinking Water Depot entrepreneurs based on local wisdom values in the form of huyula (help)